Primary Care in breast cancer screening in Brazilian women: The enhancement of radiological protection during mammography examination (Research, Society and Development, 2023)
Breast cancer is a worldwide known disease, and for a long time it affects Brazilian women. This study seeks to analyze the importance of primary care in breast cancer screening in Brazilian women, listing care for radiological protection during mammography. This is an integrative, descriptive, retrospective review with a qualitative approach, carried out on the internet with the help of Google Scholar, from November to December 2022. The research was carried out by consulting the following keywords and the connector Boolean AND: primary care AND mammography AND radiological protection END breast cancer in Brazilian women. Inclusion criteria: freely available texts; search time (2012 to 2022); target population (Brazilian women); type of study (without delimitation); Portuguese language). Data extracted in an explanatory table (title, author, year of publication, objective). At the end, a total of 11 texts were obtained. The findings were presented in topics: Emphasis on breast cancer in Brazil; relevance of early detection of breast cancer; knowledge as a tool to combat breast cancer and mammography.